The effectiveness of the various light trap colour to attract and control the insect pests population in paddy field / Muhammad Razif Ramli - Ramli, Muhammad Razif (Faculty of Plantation and Agrotechnology, 2018)
Paddy is one of main crop in Malaysia that have a problem in maintaining the profitability because the paddy expose to the pests and disease damages if there are no controls as well as possible. Therefore, this study was carried out to demonstrate the abundance of insect pests by using different colors of light traps in paddy fields. There are various types of light traps was installed in each site which are yellow, blue and green color. The light trap method was used to collect the sample of nocturnal insects for two hours per day at each site. This study conducted in paddy fields that located in Terengganu and the area that tested is about one acre. The distances between each light trap is about 12 m and arranged systematically. The data were collected by weekly basis in five weeks. The number of insects that were attracted to each type of lighting and diversity of insect population in paddy fields were recorded and analyzed. As a result, this study obtained 158 individual of insects was collected in one month. There were 7 orders of insects that had been recorded by all colors of light traps. There is significant different between population of insect and color light by weekly basis of sampling. The diversity of insects in yellow light trap was more than others and the highest order insect’s in the paddy fields were dominated by Lepidoptera and followed by Coleoptera and Hemiptera. This method as a first action should be taken to know their diversity of insect pest before proceed to the next method like using the insecticides as a chemical method to control the insect pest population.